Sexual Violence in Childhood and Post-Childhood: The Experiences of Young Men Who Have Sex With Men in Beirut - El Khoury, Cynthia (Journal of interpersonal violence, 2021)
Sexual violence has been found to have psychosocial and sexual ramifications for men who have sex with men (MSM) but has not been studied in the Middle East. We assessed the prevalence and correlates of experiences of child and post-child sexual violence among young MSM residing in Beirut, Lebanon. In total, 226 MSM, aged 18 to 29, were recruited with long-chain peer referrals and administered a survey that included questions on history of being pressured to have sex, as well as specific forms of sexual harassment and abuse, in addition to measures of psychosocial functioning and sexual behavior. Logistic regression analysis was used to examine correlates of child sex abuse and experiences of sexual violence post-childhood; 17.3% experienced sexual abuse as a child (below age 13), while 63.3% experienced any form of sexual violence post-childhood—furthermore, 48.7% had experienced being forced or pressured to have sex during their lifetime, including 32.3% prior to age 18. Participants who experienced child sex abuse were more likely to experience abusive relationships in adulthood, as well as at least one type of sexual harassment/abuse post-childhood. Experience of any sexual violence post-childhood was correlated with greater recent sexuality-related discrimination and more recent male sex partners. These findings reveal a high prevalence of sexual violence among MSM in Beirut, both in childhood and post-childhood. More research within the Middle East is needed to better understand the drivers of sexual violence in this population, and how to best provide prevention and coping services.